Giant posterior mediastinal goitergiant posterior mediastinal goiter - Muhammad H Mujammami; Aishah A Elkhzaimy; Abdulaziz A Alodhayani; Sarah M Aljasser; Abdulaziz A Alsaif (Wolters Kluwer Medknow Publications, 2020)
Vast majority of mediastinal goiters are situated in the anterior mediastinal compartment and rarely located in the posterior mediastinum. Posterior mediastinal goiters should be differentiated from other mediastinal masses through appropriate work-up by the computed tomography which is the most valuable technique. We reported a case of symptomatic mediastinal goiter extending from the neck to the posterior mediastinum compressing the trachea and airway. The surgical intervention is considered the treatment of choice in such cases. The surgical approach was done through a classical transverse cervical incision, lateral right thoracotomy, and median sternotomy. The histopathological report was consistent with a multinodular goiter. The patient's recovery was uneventful with an excellent postoperative symptomatic relief.